Stabilisation of large motions of Euler–Bernoulli beams by boundary controls - Do, Khac Duc (Taylor and Francis, 2018)
This paper proposes a design of boundary controls for stabilisation of Euler–Bernoulli beams with large motions and non-neglectable moment of inertia under external loads. Common types of boundary conditions in practice are considered. The designed boundary controllers guarantee globally practical K∞-exponential stability of closed-loop system. The control design, well-posedness and stability analysis are based on two Lyapunov-type theorems developed for a class of evolution systems in Hilbert space.